Pengaruh Online Customer Review, Promo Special Event Day, Dan Star Seller Terhadap Keputusan Pembelian Pada Marketplace Shopee - Candra Kurniawati Ningsih; Eka Farida; Kartika Rose Rachmadi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The aim of this study is to determine the effect of online customer reviews, special event day promotions and purchasing decisions of star vendors in Shopee Marketplace. The data used in this study used primary data to determine the number of active business students and distributed surveys and secondary data to the participants. The universe of this study was the students of Malang Islamic University Faculty of Economics in 2019, 2020 and 2021, while the sample of this study was 70 participants according to certain criteria. The analytical method used in this study is a multi -linear analysis that uses F tests and T tests to test hypotheses. Research shows that it has a significant impact on purchasing decisions at the Shopee Marketplace. On the other hand, online customer reviews and special event day promotions have a significant impact on the purchasing decisions of Shopee Marketplace, and star sellers may not affect the purchasing decisions of Shopee Marketplace. Keywords: Online Customer Reviews, Special Event Day Promos, Star Sellers